It’s Not Just a Pay Gap: Quantifying the Gender Wage and Pension Gap at a Post-Secondary Institution in Canada - Smith-Carrier, Tracy; Penner, Marcie; Cecala, Aaron L.; Agócs, Carol (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
What is the impact of the gender pay gap in academia over the course of a career and retirement? To quantify this impact, we used a Canadian post-secondary institution as a case study and simulated the effects of the reported difference in salary across multiple academic career trajectories. A starting wage gap of less than $9,000 resulted in a $300,000–$400,000 gender wage gap over the course of a career, and a further $148,000–$259,000 gender pension gap, for a total gender pension and wage gap of $454,000–$660,000, depending on the rank achieved. Thus, focusing on gender gaps in salary alone leads to a substantial underestimation of the long-term effects of the gender gap.